Energy efficiency and the direct and indirect effects of energy audits and implementation support programmes in Germany. (October 2021) - Schubert, Torben; Breitschopf, Barbara; Plötz, Patrick
Abstract: Energy audits help to increase energy efficiency in industry and have proven effective in many studies. Additional implementation support programmes providing financial incentives have been developed to not only support audits but also to overcome financial barriers to energy efficiency investments. Because the different types of programmes coexist, we argue that a precise analysis of their effects must explicitly model them together, demonstrating non-trivial direct and indirect effects of both audits and financial programmes on the adoption of energy efficiency measures. We corroborate the presence of these direct and indirect effects with data on German firms, all of which have participated in an energy audit programme and some of which have additionally received financial implementation support. Audits not only affect the adoption of energy efficiency measures directly, they also increase the likelihood of receiving financial implementation support, which in turn increases the adoption rate. Furthermore, our findings highlight that consultancy during implementation is an important factor for adoption. Accordingly, additional supporting policies should be considered in future energy audits, for example to ensure assistance during implementation. Highlights: We jointly model the effect of several energy efficiency programmes. We show direct and indirect effects of energy efficiency policies. Energy consultancy complements financial instruments. Consistent policies strengthen the impact of individual programmes.